PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIA 1 MAN 1 PEKANBARU - Syintia Dewi Ananta Shinta Dewi; Zulkarnain Zulkarnain; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a class action research that aims to improve the learning process and to increase mathematics achievement from the students with applied discovery learning model. The subject of this research is the students of class XI MIA 1 MAN 1 Pekanbaru at the first semester in academic year 2018/2019, which total of participants are 31 students, consists of 11 male students and 20 female students with heterogeneous ability. This research has two cycles. Each cycle has four meetings and one test. The instruments used in this research were learning instruments and the instruments of collecting data. The learning instruments used include syllabus, lesson plan, and student work sheets, while the instruments of collecting data were observation sheets and learning outcome test. The data analysis of students and teacher activity showed that the learning process has improved after the discovery learning model being implemented. The data of the student’s evaluation test showed that the persentage of students reached the Minimum Mastery Criteria (MMC) increase from the basic score to first test, from first test to second test. The results of this research showed an increasing of students achievement where the basic score 29,0% to the first test 48,4%, the second test 74,2%. For the skills achievement score of the first test 71,0%, the second test 90,3%. Based on data analysis, it can be concluded that the implementation of discovery learning model can improve learning process and increase student’s mathematics achievement at class XI MIA 1 MAN 1 Pekanbaru.